Effect of a Seeding System on Competitive Performance of Elite Players During Major Tennis Tournaments - Cui, Yixiong; Zhao, Yue; Liu, Haoyang; Gómez, Miguel-Ángel; Wei, Ran; Liu, Yuanlong (Frontiers in Psychology, 2020)
The performance of professional tennis players in the four major Grand Slam tournaments has always been an important research topic, which advances the understanding of the current development of tennis. However, there is little known about the difference between higher-ranked and lower-ranked players, considering match performance statistics. The study was aimed to explore the technical, tactical and physical performance indicators that best discriminate seeded and non-seeded male players in Grand Slams. A total of 549 matches played by 189 individual players during 2015-2017 four Grand Slams men’s singles were sampled, with corresponding match statistics gathered for each player observation, concerning players’ serving, returning, net-point, break point, efficiency and physical performance. The results showed that the seeded players outperformed the non-seeded players in serve and return, break point, net point and efficiency related indicators; while the following indicators contributed most to the separation of two player categories: seeded and non-seeded: serve and return of serve points won (%), ace (%), peak serve speed, first serve speed, net points won (%), break point per return game, break point saved, winner and unforced error ratio and dominance ratio.. Seeded players generally outperformed the non-seeded in all match performance indicators and Tthe research findings evidenced the decreased competitive balance in men’s competition during Grand Slams due to rank-based seeding system, whereas may help coaches for could use the information to and players conduct a fine-tune the training more comprehensive post-match evaluation, as well as develop benchmarks for training and match planning.